MOTIVASI DALAM MENINGKATKAN SEMANGAT KERJA DAN KINERJA USAHA PETANI PADI LOKAL LAHAN PASANG SURUT DI DESA SP1 TANJUNG BUKA - Dewi Qomariah Imelda; Tati Hariyati; Atut Seno Prasetyo (Universitas Lambung Mangkurat, 2021)
This study aims to analyze the effect of motivation on work spirit and business performance of farmers in SP1 Tanjung Buka, Tanjung Selor District. This study uses a quantitative approach by using a survey method. Implementation time is carried out for six (6) months. The Slovin formula was used to determine the research sample, and a sample of 100 farmers was obtained. The data was processed using the Structural Equation Modeling (SEM) analysis tool. The results showed that motivation had a significant positive effect on work morale, motivation had a significant positive effect on business performance and work morale had a significant positive effect on business performance. The indirect effect of motivation on business performance with intervening morale has a significant effect. The influence of the motivation variable and the work spirit variable affects the variation of the data on the business performance variable by 36%, the remaining 64% is influenced by other factors outside this study, while the influence of the motivation variable affects the variation of the data on the work morale variable, the remaining 87% is influenced by other factors.